Accounting and Financial Literacy to Improve the Capability and Quality of Human Resources in Sharia Savings and Loans Cooperatives - Titis Wahyuni (Jurnal Sosial Humaniora Terapan, 2020)
Sharia savings and loan cooperatives have business activities in the investment and savings financing sector in accordance with the concept of profit sharing or sharia. Sharia savings and loan cooperatives provide benefits for Muslims who need immediate funds for investment and business development without being subject to usury. Good accounting skills and financial literacy are needed for the managers of sharia savings and loans cooperatives so that they can avoid financing failures that can lead to the closure of the cooperative. Limited accounting skills and financial literacy for managing sharia savings and loans cooperatives have caused many sharia savings and loan cooperatives to close due to failure in managing cooperatives. The research method used in this research is descriptive method with data collection techniques through surveys of the management of savings and loan cooperatives in Depok, West Java. The results of this study indicate an increase in accounting and financial literacy skills for cooperative managers in the Depok area as well as the formation of attitudes / awareness to continue to improve accounting and financial literacy skills in managing cooperatives. However, information technology assistance is needed to assist managers in knowing the (financial) health condition of savings and loan cooperatives immediately so that the cooperative can operate and provide benefits to the community.Keywords: accounting and financial literacy, sharia savings and loan cooperatives, health assessments, financial reports, sharia